Perfil das internações por condições sensíveis à atenção primária relacionadas à cobertura da estratégia saúde da família em Anápolis-go, de 2001 a 2017 - Jéssica Caixeta Silva Sampaio; André Guimarães Araujo; Felipe Zibetti Pereira; Helen de Lima; Rafael Souto (UniEVANGÉLICA, 2018)
Objective: This study aims to describe and analyze the relationship between the coverage of the Family Health Strategy (ESF) and the Hospitalizations for Primary Care Sensitive Conditions (ICSAP) in Annapolis from 2001 to 2017. Methods:Ecological, descriptive and analytical study . We considered ICSAP occurred in Annapolis, from 2001 to 2017, analyzing the variables age, year, sex and their interrelationships. These data were extracted from the Hospital Information System (SIH / SUS) and the Basic Attention Information System (SIAB). They were also analyzed by measures of central tendency. The hospitalizations were defined through the Brazilian List of Hospitalizations for Conditions Sensitive to Primary Care.Results:FHR coverage increased 5-fold, while HFSS reduced by 3-fold compared to year 2001. The most prevalent etiologies of HFPS were: Pneumonia, Gastroenterocolitis, Asthma, Heart Failure, Angina. The "r" value attributed to the relation of the affections and the FHT were negativewhereas only the pneumonia presented r = + 0.37. The correlation between ICSAP and FHT was -0.7, while Hospitalization for Non-Primary Care Causes (N-ICSAP) was +0.26. Gastroenterocolitis accounted for 76.26% of ICSAP. Angina and Heart Failure predominated in patients older than 60 years. Asthma accounted for 57.66% of admissions in up to 9 years, while pneumonia was prevalent in all age groups. Women interned about 8 times more than men. Conclusions:The study concluded that there is an inversely proportional relationship between FHT and ICSAP in the municipality of Anápolis.